A Cation‐Exchange Approach for the Fabrication of Efficient Methylammonium Tin Iodide Perovskite Solar Cells. Issue 20 (2nd April 2019) - Li, Fengzhu; Zhang, Chaoshen; Huang, Jin‐Hua; Fan, Haochen; Wang, Huijia; Wang, Pengcheng; Zhan, Chuanlang; Liu, Cai‐Ming; Li, Xiangjun; Yang, Lian‐Ming; Song, Yanlin; Jiang, Ke‐Jian
Abstract: Tin‐based halide perovskite materials have been successfully employed in lead‐free perovskite solar cells, but the overall power conversion efficiencies (PCEs) have been limited by the high carrier concentration from the facile oxidation of Sn 2+ to Sn 4+ . Now a chemical route is developed for fabrication of high‐quality methylammonium tin iodide perovskite (MASnI3 ) films: hydrazinium tin iodide (HASnI3 ) perovskite film is first solution‐deposited using presursors hydrazinium iodide (HAI) and tin iodide (SnI2 ), and then transformed into MASnI3 via a cation displacement approach. With the two‐step process, a dense and uniform MASnI3 film is obtained with large grain sizes and high crystallization. Detrimental oxidation is suppressed by the hydrazine released from the film during the transformation. With the MASnI3 as light harvester, mesoporous perovskite solar cells were prepared, and a maximum power conversion efficiency (PCE) of 7.13 % is delivered with good reproducibility. Abstract : High‐quality, pinhole‐free CH3 NH3 SnI3 films are achieved from pristine NH2 NH3 SnI3 perovskite, and the oxidation of Sn 2+ to Sn 4+ can be efficiently suppressed owing to the reduction agent hydrazine generated inside the films in the conversion. With the CH3 NH3 SnI3 film as light absorber, mesoporous MASnI3 perovskite solar cells were fabricated with a maximum PCE of 7.13 %.